Rhabdomyolysis Complicating Typhoid Fever in a Child and Review of the Literature. Issue 9 (September 2017) - Snelling, Peter James; Moriarty, Paul; Vaska, Vikram L.; Levitt, David; Nourse, Clare
Abstract : Typhoid fever is an important cause of morbidity and mortality in the developing world, particularly in children, but is infrequently observed in the developed world and can occur in patients without a significant travel history. Rhabdomyolysis as a complication has rarely been reported, and never in a child. A child with Salmonella enterica serovar Typhi septicemia, complicated by rhabdomyolysis, encephalopathy and pancreatitis is described and all 15 reported cases to date are summarized. Abstract : Supplemental Digital Content is available in the text.